Guest Editorial (American Journal of Islam and Society, 2019)
The papers in this special issue and the one preceding it have their roots in a panel titled “Ethnography, Misrepresentations of Islam, and Advocacy,” which Timothy Daniels and I organized for the 116th Annual Meeting of the American Anthropological Association. We were joined on this panel by Alisa Perkins, Katrina Thompson, Robert Hefner, and Yamil Avivi, where we all grappled with our struggles with the increasingly political nature of our work on Islam. Although we work in a variety of geographic regions, with diverse subjects, we all shared similar concerns regarding the complexity of accurately depicting the Muslim communities we study while challenging the anti-Muslim stereotypes that exist in popular culture and contemporary news media. At the same time, we did not wish to reify popular divisions between “good” and “bad” Muslims or inaccurately depict the lives of our research subjects in order to cater to that popular division.To download full editorial, click on PDF.